{Human Papilloma Virus infection in sexually active adolescent girls} - Michala, L.; Argyri, E.; Tsimplaki, E.; Tsitsika, A.; Bakoula, C.; Antsaklis, A.; Panotopoulou, E. (Gynecologic Oncology, 2012)
Purpose: Adolescents are a vulnerable group with regard to sexually transmitted infections, including Human Papilloma Virus (HPV). This is thought to be both because of their more liberal sexual behavior and also the relative immaturity of their genital tract. The aim of the study was to examine trends in HPV infection among sexually active adolescents attending for a sexual health screen. Methods: Sexually active adolescents were offered cervical screening, HPV typing and conventional genital cultures as part of a sexual health prevention protocol. Participating adolescents also completed a sexual health questionnaire. Results: Between January 2008 and July 2011, 149 sexually active girls were examined for reproductive health issues (mean age 17.3 years). 62 (42{%}) tested positive for HPV DNA, 30 were infected by multiple types and 54 had at least one high risk type identified. The most commonly identified HPV DNA was for low risk type 42 (15 cases, 7.8{%}), followed by high risk types 51 (14 cases, 7.3{%}) and 59 (11 cases, 5.7{%}). E6-E7 mRNA expression was detected in 16 girls (11{%}), of which half were for HPV 16. Girls who tested positive for HPV DNA and mRNA had similar age at sexual debut with those that tested negative (15.1 years in all groups) but had on average more sexual partners (4.1 vs1.9 p = 0.007). Only 9 girls in this cohort had been vaccinated against HPV. Approximately half of the girls reported using inadequate or no contraception. Conclusions: HPV infection rate was high in our sample. Furthermore a high percentage was infected with high risk types and a proportion of girls demonstrated mRNA HPV expression. As age at first sexual intercourse drops, vaccination against HPV and sexual education should be instituted in early adolescence, in order to reduce long term reproductive sequelae of unsafe sexual practices. © 2012 Elsevier Inc. All rights reserved.
Keywords: Adolescent sexual health; HPV DNA typing; HPV infection